Sample pooling on the Cepheid Xpert R Xpress SARS-CoV-2 assay (2020)
The COVID-19 pandemic has placed unprecedented global demand on laboratory supplies required for testing. Sample pooling has been investigated by laboratories as a strategy to preserve testing capacity. We evaluate the performance of Cepheid Xpert® Xpress SARS-CoV-2 RT-PCR assay for testing samples in pools of four and six. Clinical samples containing SARS-CoV-2, and confirmed negative clinical samples were used to create sample pools. Clinical samples had ‘neat’ Xpert® E gene cycle threshold (Ct) values ranging between 20 and 28 and all were detected qualitatively when contained in pools of four or six samples. For these samples, pooling had a median change in Ct value of 2.0 in pools of four, and of 2.9 in pools of six. With the use of Cepheid Xpert® Xpress SARSCoV-2 RT-PCR assay, pooling of four or six samples may be an effective strategy to increase testing capacity.